Quality of brown-shelled eggs marketed in different commercial establishments - Souza, Thiago; Lopes, Claudia da Costa; Vieira, Rita Brito; Santos, Gabriela Coelho; Silva, Rodrigo Ferreira; Calixto, Ediane Santos; Azevedo, Jaine Alves (Acta Scientiarum. Animal Sciences, 2020)
This study aimed at evaluating the internal and external quality of brown-shelled eggs commercialized in the municipality of Parintins-AM. A total of 540 eggs were evaluated and distributed in a completely randomized design, which consisted of three treatments and six replications of 30 eggs each. The treatments were: eggs sold in supermarkets; in grocery stores; and eggs sold directly at the farm. The age of the eggs from supermarkets and grocery stores was unknown, however, the eggs bought at the farm were marketed as being from the day of laying. The collected data were submitted to analysis of variance and Tukey test at 5% probability. There were no differences (p > 0.05) of treatments in the percentage of dirty eggs, however, grocery and farm eggs presented higher (p < 0.05) crack percentage. The eggs at the farm presented higher incidence (p < 0.05) of internal stains of blood. The weight of the egg and albumen presented no differences (p > 0.05). However, the albumen percentage of the farm eggs was higher than the other treatments (p < 0.05). The percentages for yolk and eggshell weight from the farm eggs were lower than the supermarket and grocery eggs (p < 0.05). For the variables albumen height, Haugh unit, albumen index, yolk and albumen pH, the best results were observed for the farm eggs, however, regarding these variables, eggs sold in supermarkets and grocery stores did not differ from each other. The brown shell eggs sold in the city of Parintins/AM have high rates of external defects, and the eggs bought directly from the farm presented better internal quality, when compared to eggs sold in different establishments.